Modelo matemático para a definição de embalagens industriais: estudo de caso em uma empresa automobilística - (:unkn) unknown (Universidade Federal de Goiás, 2016)
The procedure for determining the use of industrial packaging to a particular item is becoming more common in companies seeking to suit the conditions and needs of the costumer market, i.e., products that are marketed must from time to time be updated and / or replaced by new concepts. In the automotive industry, the launch of new vehicles has, in general, updated at least once a year, that is, for those responsible in determining the type of packaging to be used in the logistics flow there is always the need to analyze, define and implement new concepts in packaging. The objective of this paper is to propose a mathematical model that allows one to define the type of packaging to be used, considering the specifications of the part, assembly, and all its movement along the supply chain, minimizing the internal handling cost. The rationale for this work is linked to the constant need for packaging process definition, caused by the upgrading of products and process optimization. The difficulty is encountered when the process increases due to design of greater complexity with a high number of pieces and it influences the supply and assembly. This paper aims to conduct applied research, to study a practical problem and provide relevant expertise. Thus, the approach of quantitative research is due to the fact that it uses information that can be translated into numbers, in order to analyze and make the right conclusions. Thus, the research is exploratory as it involves a literature review on the theme, seeking authors that made related or similar studies. The mathematical model developed in this study was implemented in a vehicle assembler, and it was possible to verify the 50.27% reductions on internal handling costs given the solutions proposed by the integer programming model.
Mathematical model for the definition of industrial packaging: a case study in a company automotive
Keywords: Embalagem; Custo de movimentação; Programação inteira; Setor automobilístico; Package; Internal handling cost; Integer programming; Automotive industry; CIENCIAS EXATAS E DA TERRA::MATEMATICA